Hubungan Penggunaan Gadget Terhadap Konsentrasi Belajar Pada Anak Usia Sekolah Di SDN Cibogo Kecamatan Cisauk Kabupaten Tangerang - Suroso Suroso; TantriWenny Sitanggang; Oom Komalasari; Fareza Putri Azis (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction : The excessive use of gadgets by students sometimes often causes problems in the learning process resulting in a decrease in learning concentration in children, especially school-age children. Gadget use has a detrimental effect on children's interpersonal skills if used too often. Another influence of mobile phones on student learning achievement is that students become more dependent on mobile phones rather than having to study. The purpose of research : In this study to determine the relationship between the use of gadgets and the concentration of learning in children aged at SDN Cibogo, Cisauk District, Tangerang Regency. Research methods : The research design is quantitative analytic with a cross sectional study approach. The sample in this study were school-age children using stratified random sampling technique with 53 respondents from a total population of 300 people at Cibogo Elementary School, Cisauk District, Tangerang Regency. Results of research : Shows high Gadget Use with high Learning Concentration as much as 7 with a percentage (26.9%), if respondents who have High Gadget Use with Low Learning Concentration are 19 with a percentage (73.1%), while respondents who have Low Gadget Use with Concentration 17 with a high learning percentage (63.0%), and respondents who have low gadget use with a low learning concentration are 10 with a percentage (37.0%). Conclusion : There is a significant relationship between the use of gadgets and the concentration of learning in students of SDN Cibogo, Cisauk District, Tangerang Regency. and the results of the Odds Ratio (OR) 4.61 (1.4-14.8) indicate that respondents who have high use of gadgets will be at risk of experiencing low learning concentration. compared to respondents who have Low Gadget Use.